Multiple sclerosis and alcohol use disorders: in-hospital mortality, extended hospital stays, and overexpenditures - M. Gili-Miner; J. López-Méndez; A. Vilches-Arenas; G. Ramírez-Ramírez; D. Franco-Fernández; J. Sala-Turrens; L. Béjar-Prado (Neurología (English Edition), 2018)
Introduction: The objective of this study was to analyse the impact of alcohol use disorders (AUD) in patients with multiple sclerosis (MS) in terms of in-hospital mortality, extended hospital stays, and overexpenditures. Methods: We conducted a retrospective observational study in a sample of MS patients obtained from minimal basic data sets from 87 Spanish hospitals recorded between 2008 and 2010. Mortality, length of hospital stays, and overexpenditures attributable to AUD were calculated. We used a multivariate analysis of covariance to control for such variables as age and sex, type of hospital, type of admission, other addictions, and comorbidities. Results: The 10 249 patients admitted for MS and aged 18-74 years included 215 patients with AUD. Patients with both MS and AUD were predominantly male, with more emergency admissions, a higher prevalence of tobacco or substance use disorders, and higher scores on the Charlson comorbidity index. Patients with MS and AUD had a very high in-hospital mortality rate (94.1%) and unusually lengthy stays (2.4 days), and they generated overexpenditures (1116.9 euros per patient). Conclusions: According to the results of this study, AUD in patients with MS results in significant increases in-hospital mortality and the length of the hospital stay and results in overexpenditures. Resumen: Introducción: El objetivo de este estudio es el análisis del impacto de los trastornos asociados al consumo de alcohol (TCA) en los pacientes con esclerosis múltiple (EM), en términos de exceso de mortalidad intrahospitalaria, prolongación de estancias y sobrecostes. Métodos: Estudio observacional retrospectivo de una muestra de pacientes ingresados con EM recogidos en los conjuntos mínimos básicos de datos de 87 hospitales españoles durante el periodo 2008-2010. Se calculó la mortalidad, la prolongación de estancias y los sobrecostes atribuibles a los TCA controlando mediante análisis multivariado de la covarianza variables como la edad y el sexo, el tipo de hospital, el tipo de ingreso, otros trastornos adictivos y las comorbilidades. Resultados: Se estudiaron 10.249 ingresos por EM de 18 a 74 años de edad, entre los cuales hubo 215 pacientes con TCA. Los ingresos con EM y TCA fueron predominantemente varones, mayor frecuencia de ingresos urgentes, con mayor prevalencia de trastornos por tabaco y drogas y con índices de comorbilidad de Charlson más elevados. Los pacientes con EM y TCA presentaron importantes excesos de mortalidad (94,1%), prolongación indebida de estancias (2,4 días) y sobrecostes por alta (1.116,9 euros). Conclusiones: De acuerdo a los resultados de este estudio, los TCA en pacientes con EM aumentaron significativamente la mortalidad, la duración de la estancia hospitalaria y sus costes. Keywords: Multiple sclerosis, Alcohol use disorders, Mortality, Hospital stay, Costs, Palabras clave: Esclerosis múltiple, Trastornos asociados al consumo de alcohol, Mortalidad, Estancia hospitalaria, Costes